2017
DOI: 10.1080/10810730.2017.1411996
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reproductive Health-Related Information-Seeking Behavior of Low-Income Women: Describing a Two-Step Information-Seeking Process

Abstract: This paper explores the reproductive health-related information seeking of low-income women that has been found to be affected by digital divide disparities. A survey conducted with 70 low-income women explores what information sources women use for reproductive health-related information seeking, what process they go through to find information, and if they are using sources that they trust. The findings of this study detail a two-step information-seeking process that typically includes a preference for perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
3
18
0
3
Order By: Relevance
“…African American and Black women are at increased risk of poor maternal health outcomes, including risks impacted by nutrition and health status. African American and Black women are likely to seek health information predominately from informal sources, such as social media and members of their social network ( 8 , 9 ). Health disparities, longstanding institutional and structural barriers, and mistrust or lack of cultural awareness during the clinical encounter may contribute to the patient-provider communication gap.…”
Section: Introductionmentioning
confidence: 99%
“…African American and Black women are at increased risk of poor maternal health outcomes, including risks impacted by nutrition and health status. African American and Black women are likely to seek health information predominately from informal sources, such as social media and members of their social network ( 8 , 9 ). Health disparities, longstanding institutional and structural barriers, and mistrust or lack of cultural awareness during the clinical encounter may contribute to the patient-provider communication gap.…”
Section: Introductionmentioning
confidence: 99%
“…Many women in developed countries describe constantly going online for information and peer support about pregnancy and caring for infants and young children [ 15 21 ]. It is important to note, however, that research has found that some social groups, such as low-income women in areas of the USA, rarely use the internet for health information, preferring to call upon family and friends [ 22 , 23 ]. A survey of American middle-aged and older women with chronic health conditions [ 24 ] found that while 65% of them reported using the internet to find information or seek advice from others, older women were much less likely to use the internet for these purposes.…”
Section: Introductionmentioning
confidence: 99%
“…This would facilitate the empowerment of women and self-management of their health. Internet tools are commonly used by women from all social strata [54, 62] and in some cases they represent the main source of information on pregnancy and the postpartum period, such as in the case of highly qualified and/or immigrant women, for whom going to maternal education sessions is not always feasible [8, 53].…”
Section: Resultsmentioning
confidence: 99%